Surface ozone concentration trends and its relationship with weather types in Spain (2001–2010). (January 2015) - Santurtún, Ana; González-Hidalgo, José Carlos; Sanchez-Lorenzo, Arturo; Zarrabeitia, María Teresa
Abstract: This paper assesses the temporal variations of surface ozone concentrations during the period 2001–2010 in 3 regions of Spain with different geographical and socioeconomic features (northern coastland, central inland and northeast inland), as well as its link with atmospheric circulation. Specifically, daily surface atmospheric patterns over the aforementioned regions are characterized using NCEP/NCAR reanalysis data and an objective classification scheme in order to study the relationship between synoptic weather types and daily ozone levels. The results show that tropospheric ozone concentration has a tendency towards an increase during the study period, both during daytime and nighttime. Moreover, in general, this upward trend is seen throughout all of the seasons. The observed trends are in line with a reported decrease of NO X emissions and increase in surface solar radiation during the 2000s in Spain. On the other hand, interestingly, median concentrations were statistically significantly lower in days with anticyclonic weather conditions than in the rest of meteorological situations, while days with a directional weather type showed higher median levels of ozone concentration, with maximum values in days with northern and eastern component. Due to the detrimental effect that ozone has on human health, the relationship between synoptic weather patterns and daily ozone levels shown in this work could potentially be used for implementing pollution level alert protocols depending on forecast weather types. Highlights: Tropospheric ozone concentration shows an upward trend throughout all seasons. Ozone upward trend is in line with a reported decrease of NO X emissions and with an increase in surface solar radiation. Synoptic meteorology is associated with ozone levels. Median concentrations were significantly lower in days with Anticyclonic weather.